2006
DOI: 10.1017/s001216220600079x
|View full text |Cite
|
Sign up to set email alerts
|

Early motor development and later language and reading skills in children at risk of familial dyslexia

Abstract: Relationships between early motor development and language and reading skills were studied in 154 children, of whom 75 had familial risk of dyslexia (37 females, 38 males; at-risk group) and 79 constituted a control group (32 females, 47 males). Motor development was assessed by a structured parental questionnaire during the child's first year of life. Vocabulary and inflectional morphology skills were used as early indicators of language skills at 3 years 6 months and 5 years or 5 years 6 months of age, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
53
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 27 publications
6
53
0
5
Order By: Relevance
“…This result is in line with previous studies (8,23,25), but contradictory results have also been reported. For example, Shapiro et al (38) indicated that reading delay is better predicted using infant language measures than using measures of early motor development.…”
Section: Discussionsupporting
confidence: 92%
“…This result is in line with previous studies (8,23,25), but contradictory results have also been reported. For example, Shapiro et al (38) indicated that reading delay is better predicted using infant language measures than using measures of early motor development.…”
Section: Discussionsupporting
confidence: 92%
“…We have very recently analyzed our data collected from the motor domain and found support for its potential role in the early developmental risk profile of a subgroup of children by detecting an early motor delay that is associated with language development and a delay in acquiring fluent reading skill (Viholainen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to right the head is essential to achieving postural control. Preterm infants have a heightened risk for motor problems, and early postural control, related to head lag in pull-to-sit, can be an important predictor of developmental outcome (Samsom & de Groot, 2000;Viholainen et al, 2006). Persistent head lag beyond age 4 mo has been linked to poor outcomes (Flanagan, Landa, Bhat, & Bauman, 2012), but few studies have investigated head lag during the neonatal period (Barbosa, Campbell, Smith, & Berbaum, 2005;Karmel et al, 2010).…”
mentioning
confidence: 99%